Combination of growth factor treatment and scaffold deposition following traumatic brain injury has only a temporary effect on regeneration - Clausen, Fredrik; Lindh, Tone; Salimi, Shabnam; Erlandsson, Anna (Brain research, 2014)
The recovery after traumatic brain injury (TBI) is hampered by the poor regenerative capacity of the brain. Today there is no treatment available that effectively restores lost brain tissue, but much research is focused on the stimulation of endogenous neural stem cells to viably and functionally repopulate the injured parenchyma. It is crucial that the therapies have a proven long-term effect on both regeneration and functional recovery to be clinically interesting. Here we have studied the induction of stem cell activation in rats at three weeks and six weeks after inducing TBI using controlled cortical impact model at a severe setting. We combined intracerebroventricular growth factor and scaffold treatment in order to accomplish an optimal effect on the stem cell regeneration. Immediately after TBI epidermal growth factor infusion with osmotic minipumps was started and continued for seven days. The pumps were removed and an extracellular matrix scaffold containing vascular endothelial growth factor was deposited into the cortical cavity. Three weeks after injury there was a positive effect of the treatment with a significant increase in neuronal and astrocytic regeneration. However, after six weeks there was no difference in the number of newly generated neurons and astrocytes in treated or untreated rats. Evaluation of tissue loss and spatial learning in the Morris water maze corroborated that the treatment had no effect at the later time point. Our results highlight the importance of long-term studies to ensure that a promising effect on tissue regeneration and functional outcome is not only temporary. •Growth factor and scaffold treatment increased regeneration three weeks after TBI.•After six weeks there was no effect on the number of new neurons and astrocytes.•The treatment enhanced spatial learning after two weeks, but not after five weeks.•Our data show the importance of studying regeneration over longer periods of time.